A study of inhibition and reversal of plasmodium falciparum cytoadherence using RNA apatamer specific to ICAM-1 /CD54 and CD36 protein - Mustaffa, Khairul Mohd Fadzli (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2018)
Malaria is a life-threatening parasitic infection occurring in the endemic areas,. primarily in children under the age of five, pregnant women, and patients with human immunodeficiency virus and acquired immunodeficiency syndrome (HIV) /(AIDS) as well as non-immune individuals. The cytoadherence of infected erythrocytes (IEs) to the host endothelial surface receptor is a known factor that contributes to the increased prevalence of severe malaria cases due to the accumulation of !Es, mainly in the brain and other vital organs. Therefore, further study is needed to discover a new potential anti-adhesive drug to treat severe malaria thus reducing its mortality rate. In this review, we discuss how the aptamer technology could be applied in the development of a new adjunct therapy for current malaria treatment.